Changing maternal, infant and young child nutrition practices through social and behaviour change interventions implemented at scale: Lessons learned from Alive & Thrive - Valerie L. Flax; Sujata Bose; Jessica Escobar‐DeMarco; Edward A. Frongillo (Maternal and Child Nutrition)
Abstract Alive & Thrive (A&T) is an initiative designed to advance the implementation of maternal, infant and young child nutrition (MIYCN) social and behaviour change (SBC) at a large scale. The aims of this research were to: (1) describe A&T's SBC implementation processes and their impact based on a review of programme documents and peer‐reviewed publications and (2) gather lessons learned from key informant interviews (N = 23) with A&T staff and stakeholders in Bangladesh, Burkina Faso, Ethiopia, India, Nigeria and Vietnam. A&T's SBC approach used interpersonal communication, community mobilization and mass media to address knowledge gaps, strengthen self‐efficacy and shift social norms. The initiative used data for design and evaluation and facilitated scale and sustainability through close collaboration with governments and other stakeholders. A&T's approach increased exclusive breastfeeding, minimum meal frequency of children and use of iron and folic acid tablets by pregnant women, but had mixed impacts on early initiation of breastfeeding and maternal and child dietary diversity. Multiple SBC channels and frequent contacts strengthened the impact of SBC on MIYCN practices. Lessons learned included: using existing large‐scale platforms for interpersonal communication, improving counselling skills of health workers, delivering timely tailored messages, engaging key influencers to take specific actions, using research to address underlying behavioural concerns and maximize mass media reach and frequency, using simple memorable messages and employing additional channels to reach low media coverage areas. A&T developed and implemented at‐scale MIYCN SBC in multiple countries, providing lessons learned about intervention strategies, engagement of influencers and mass media campaign development, which governments and other implementers can adapt and replicate.